Heaven on earth : painting and the life to come - Clark, Timothy J. (Thames & Hudson, 2018)
Preeminent art historian T.J. Clark explores how painters since the Middle Ages have portrayed the divine on earth. In this latest work, respected art historian T. J. Clark sets out to investigate the different ways painting has depicted the dream of God’s kingdom come: heaven descended to earth. He goes back to the late Middle Ages and Renaissance―to Giotto in Padua, Bruegel facing the horrors of religious war, Poussin painting the Sacraments, and Veronese unfolding the human comedy, in particular his inscrutable Allegory of Love. Was it ultimately to painting’s advantage that in an age of orthodoxy and enforced censorship (threats of hellfire, burnings at the stake) artists found ways reflect on the powers and limitations of religion without putting their thoughts into words? In conclusion Clark brings us into the Nuclear Age with Picasso’s Fall of Icarus, made for UNESCO in 1958, which already seems to signal, or even prescribe, an age when all futures are dead.